2016
DOI: 10.1038/tp.2016.106
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Tert in the medial prefrontal cortex and hippocampus rescues aggression and depression of Tert−/− mice

Abstract: The role of telomerase reverse transcriptase (TERT) has been extensively investigated in the contexts of aging and cancer. Interestingly, Tert−/− mice exhibit additional but unexpected aggressive and depressive behaviors, implying the potential involvement of TERT function in mood control. Our conditional rescue experiments revealed that the depressive and aggressive behaviors of Tert−/− mice originate from Tert deficiency in two distinct brain structures. Reactivation of Tert in the hippocampus was sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Similarly, prenatally-stressed animals had shorter telomeres than controls in the mPFC (Blaze et al, 2017). Pivotally, a study using mice deficient for Tert, a key component of the enzyme telomerase responsible for the maintenance of telomere length, demonstrated the requirement of this telomere-regulating enzyme for mood stability (Zhou, Wu, et al, 2016). Specifically, they showed that the reexpression of Tert in the mPFC rescued the depressive phenotype of Tert −/− mice, thus revealing a novel role of Tert in emotional control in the mPFC (Zhou, Ning, et al, 2016).…”
Section: The Effect Of Prs-tl On the Facial Affect-processing Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, prenatally-stressed animals had shorter telomeres than controls in the mPFC (Blaze et al, 2017). Pivotally, a study using mice deficient for Tert, a key component of the enzyme telomerase responsible for the maintenance of telomere length, demonstrated the requirement of this telomere-regulating enzyme for mood stability (Zhou, Wu, et al, 2016). Specifically, they showed that the reexpression of Tert in the mPFC rescued the depressive phenotype of Tert −/− mice, thus revealing a novel role of Tert in emotional control in the mPFC (Zhou, Ning, et al, 2016).…”
Section: The Effect Of Prs-tl On the Facial Affect-processing Networkmentioning
confidence: 99%
“…First, DNA used to measure TL was ascertained from buccal swabs rather than from brain tissue, meaning it may have useful predictive biomarker properties, but may lack construct validity (Powell, Fernandes, & Schalkwyk, 2012 Hubacek, 2014;Friedrich et al, 2000). Furthermore, there is some animal work (Zhou, Wu, et al, 2016) which provides clues about connections between TL and the brain, but far more research is needed.…”
Section: Considerations and Conclusionmentioning
confidence: 99%
“…This function is mediated by telomeric length stability or extra-telomeric telomerase isoforms (Radan et al, 2014 ; Zeng et al, 2014 ). In particular, telomerase deficiency impairs normal brain function in mice (Lee et al, 2010 ; Zhou et al, 2016 , 2017 ). In the brain, telomerase in ASCs plays a critical role in the proliferation of NSCs, neuronal differentiation and development, and neuronal survival, which are involved in CNS diseases (Mattson and Klapper, 2001 ).…”
Section: Roles For Telomerase In Brain Developmentmentioning
confidence: 99%
“…Interestingly, NO is a gaseous neurotransmitter that has also been implicated in a wide range of pathological behaviors including aggression, anxiety, depression and cognitive functioning. NOS1 knockdown mice display a characteristic behavioral profile consisting of reduced anxiety and aggression and impaired cognitive metrics including learning and memory (Wultsch et al, 2007; Miszczuk et al, 2016; Zhou et al, 2016). Recent studies have shown that deficits of endothelial NOS1 in AD play an important role in the phosphorylation of the AD-related lesion tau in murine APP/PS1 TgAD models (Austin and Katusic, 2016) while increased NOS-1 activity and NO transmission in the hippocampus was evidenced to modulate aggression (Miszczuk et al, 2016; Zhou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…NOS1 knockdown mice display a characteristic behavioral profile consisting of reduced anxiety and aggression and impaired cognitive metrics including learning and memory (Wultsch et al, 2007; Miszczuk et al, 2016; Zhou et al, 2016). Recent studies have shown that deficits of endothelial NOS1 in AD play an important role in the phosphorylation of the AD-related lesion tau in murine APP/PS1 TgAD models (Austin and Katusic, 2016) while increased NOS-1 activity and NO transmission in the hippocampus was evidenced to modulate aggression (Miszczuk et al, 2016; Zhou et al, 2016). Again, the seemingly multiphasic bioavailability of NOS1 like that for COMT provides an equally oscillatory potential for episodic and complex behaviors such as aggression against a background of the inflammatory neurodegeneration and disorganized thinking that in part characterize cognitive disruption in AD.…”
Section: Discussionmentioning
confidence: 99%